Persepsi Kepuasan Konsumen terhadap Produk Kopi di UD. Tyyana Coffee - Sutan Pulungan; Novita Aswan; Siagian, Yudinar Ratnasari (Yayasan Literasi Sains Indonesia, 2024)
This research aims to analyze consumer satisfaction perceptions towards UD. Tyyana Coffee in Aek Sabaon Village, Tapanuli Selatan, conducted in May 2024 using accidental sampling and quantitative data analysis. Consumer satisfaction is measured based on loyalty, location, service, and coffee taste. The results show that customer loyalty falls into the